Cost-effectiveness of community-based screening and treatment for chronic hepatitis B in The Gambia: an economic modelling analysis - Dr. Shevanthi Nayagam, MBBS; Lesong Conteh, PhD; Elisa Sicuri, PhD; Yusuke Shimakawa, PhD; Penda Suso, BSc; Saydiba Tamba; Ramou Njie, PhD; Harr Njai, PhD; Maud Lemoine, PhD; Prof. Timothy B Hallett, PhD; Prof. Mark Thursz, MD (Elsevier, 2016)
Background: Despite the high burden of hepatitis B virus (HBV) infection in sub-Saharan Africa, absence of widespread screening and poor access to treatment leads to most people remaining undiagnosed until later stages of disease when prognosis is poor and treatment options are limited. We examined the cost-effectiveness of community-based screening and early treatment with antiviral therapy for HBV in The Gambia. Methods: In this economic evaluation, we combined a decision tree with a Markov state transition model to compare a screen and treat intervention consisting of adult community-based screening using a hepatitis B surface antigen (HBsAg) rapid test and subsequent HBV antiviral therapy versus current practice, in which there is an absence of publicly provided screening or treatment for HBV. We used data from the PROLIFICA study to parameterise epidemiological, primary screening, and cost information, and other model parameter inputs were obtained from a literature search. Outcome measures were cost per disability-adjusted life-year (DALY) averted; cost per life-year saved; and cost per quality-adjusted life-year (QALY) gained. We calculated the incremental cost-effectiveness ratios (ICERs) between current practice and the screen and treat intervention. Costs were assessed from a health provider perspective. Costs (expressed in 2013 US$) and health outcomes were discounted at 3% per year. Findings: In The Gambia, where the prevalence of HBsAg is 8·8% in people older than 30 years, adult screening and treatment for HBV has an incremental cost-effectiveness ratio (ICER) of $540 per DALY averted, $645 per life-year saved, and $511 per QALY gained, compared with current practice. These ICERs are in line with willingness-to-pay levels of one times the country's gross domestic product per capita ($487) per DALY averted, and remain robust over a wide range of epidemiological and cost parameter inputs. Interpretation: Adult community-based screening and treatment for HBV in The Gambia is likely to be a cost-effective intervention. Higher cost-effectiveness might be achievable with targeted facility-based screening, price reductions of drugs and diagnostics, and integration of HBV screening with other public health interventions. Funding: European Commission.